Increased Level of von Willebrand Factor Is Significantly and Independently Associated with Diabetes in Postinfarction Patients - Zareba, Wojciech; Pancio, George; Moss, Arthur J.; Kalaria, Vijay G.; Marder, Victor J.; Weiss, Harvey J.; Miller Watelet, Luc F.; Sparks, Charles E.; for THROMBO Investigators (Thrombosis and Haemostasis, 2001)
Diabetes is an established risk factor for reinfarction and cardiac death in postinfarction patients. Since the underlying mechanism of diabetes-related risk is not fully understood we aimed to evaluate the association between lipids, thrombogenic factors and diabetes in postinfarction patients. The study population consisted of 1,045 post-infarction patients (846 non-diabetic, 125 non-insulin- and 74 insulin-requiring diabetics) with the following blood tests performed 2 months after an index myocardial infarction: lipoprotein (a), apolipoprotein-B, apolipoprotein-A, cholesterol, HDL cholesterol, triglycerides, insulin, von Willebrand factor (vWF), fibrinogen, factor VII, D-dimer, and plasminogen activator inhibitor (PAI-1). After adjustment for relevant clinical covariates, non-insulin-requiring diabetes was significantly (p <0.05) associated with elevated levels of (odd ratios per 1 log unit increase in parenthesis) vWF (1.74) and PAI-1 (1.42) whereas insulin requiring diabetes was associated with even more elevated levels of vWF (4.68), but not with increased levels of PAI-1. No significant differences in lipid levels were observed among three groups. In conclusion, increased level of von Willebrand factor is significantly and independently associated with diabetes in postinfarction patients, suggesting that endothelial damage is the primary mechanisms contributing to an increased occurrence of vascular and cardiac events in diabetic postinfarction patients.
Keywords: Diabetes; Myocardial Infarction; vWF; PAI-1